Analgesic, Antidiarrheal and Antidepressant Activities of Anethum sowa Linn. in Swiss-Albino Mice Model - Mansur, Muhammad Abdullah Al; Siddiqi, M Mahboob Ali; Saha, Koushik (Bangladesh Pharmaceutical Journal, 2018)
The hexane (HE), dichloromethane (DCME), ethyl acetate (EAE) and methanol (ME) extracts of seed and stem of Anethum sowa were subjected to screenings for analgesic, anti-diarrheal and anti-depressant activities. The peripheral and central analgesic actions were determined by using formalin-induced writhing test and tail immersion method. The DCME extract of stem, at a dose of 200 mg/kg body weight, significantly reduced the number of writhing movements whereas the methanol extract of seed at the same dose exhibited remarkable analgesic activity in tail immersion method. In castor oil induced anti-diarrheal assay, the ethyl acetate extract of stem, at 400 mg/kg body weight, exhibited significant anti-diarrheal effect. In addition, significant anti-depressant activity was observed at a dose of 400 mg/kg body weight as compared to the standard drug in case of HE extract of stem. Bangladesh Pharmaceutical Journal 21(1): 1-6, 2018